2009
DOI: 10.3109/s10165-009-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and associations of sleep disturbances in patients with systemic lupus erythematosus

Abstract: The aim of this study was to analyze sleep complaints in patients with systemic lupus erythematosus (SLE) and to determine its prevalence and associations. Fifty outpatients with SLE and an equal number of age- and sex-matched controls were included in the study. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) in both cases and controls. Depressed mood, functional disability and pain severity were assessed in patients using standardized questionnaires. Disease severity, cumulative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 16 publications
3
13
0
2
Order By: Relevance
“…The results of this study are similar to previous studies reporting a prevalence of 55%-62% of sleep disturbances in patients with SLE. The study of Chandrasekhara et al [3] showed that SLE patients had more severe disturbances in almost all components of sleep quality than controls. While an association between SLE activity and sleep disturbance is expected, the results of previous studies have been different in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study are similar to previous studies reporting a prevalence of 55%-62% of sleep disturbances in patients with SLE. The study of Chandrasekhara et al [3] showed that SLE patients had more severe disturbances in almost all components of sleep quality than controls. While an association between SLE activity and sleep disturbance is expected, the results of previous studies have been different in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an association between disease activity and subjective sleep disturbances [3,5] but other studies demonstrated no clear relationship in this regard [6,7]. There are also studies indicating a major role for psychological factors, mainly depression, for sleep disturbances in SLE patients, but other psychological disorders such as anxiety are less studied [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations